Comparison between Rolled and Nonrolled U-Shaped Flap in the Second Stage of Dental Implant Surgery: A Randomized Clinical Trial - Ahmed Fadhel Al-Quisi; Osamah Mohammed Aldaghir; Hassanien A. AL-jumaily (Hindawi Limited, 2022)
Background. The presence of black triangles around the dental implant-supported prosthesis and the failure to construct adequate papillae around them bothers dental implantologists. Peri-implant surgical soft tissue management will improve esthetics, function, and implant survival. Aim. To compare the effects of rolled and nonrolled U-shaped flaps combined with a temporary crown in enhancing the soft tissue around dental implants. Materials and Methods. Forty patients were included in this study; all patients were operated on by the same maxillofacial surgeon at Al-Iraq specialized dental clinics from January 2019 to January 2020. Patients were divided randomly into two groups: group A: at the second stage of implant surgery, a U-shaped flap without rolling was used in conjunction with temporary crown placement; group B: at the second stage of implant surgery, a U-shaped flap with rolling was used in conjunction with temporary crown placement. Then, the temporary crown was fabricated for both groups and kept in place for one month. Two independent maxillofacial surgeons evaluated all patients two weeks after the cementation of the final zirconia crown for the implant soft tissue esthetic score. Results. The highest possible score assigned to the mesial papilla (2 scores) was present in 92.5% of the group A patients and only 77.5% of the group B patients. Moreover, we have found that alveolar bone contour is achieved perfectly (2 scores) in 70% of group A patients but only in 32.5% of group B patients. Conclusion. The U-shaped flap without rolling with a temporary crown is a simple technique. It has good results, especially when there is no severe resorption of the labial bone plate (in canine and premolar areas).